BEFORE LATE: LET’S ACCOMPLISH THE GREAT- AN ARGUMENT TO SAVE ENVIRONMENT WITH SPECIAL REFERENCE TO CONDITION OF NEPAL - Atindra (International Journal of Research -GRANTHAALAYAH, 2016)
Development and civilization have been top-rated priorities and indication of human success in the world; and the largest segment of world talent are immersing to mark new and ever un-experimented record in this course. But paying more attention towards money centric gain and material prosperity centric civilization, an irrational attack on environment is rife everywhere. In last few decades, the environmental strength of world has been largely damaged and it has offered severe impacts on human health now. Though, people were more over-swayed with anthropomorphic use of environment and some transitory progress gained, slowly the imbalance of environment and its reverse effects on human lives have started taking limelight of people. And now, environment seems to be equally pressing and compelling agendas of human checklist to do. If not initiated anything great, it may be more than late to save us and future generation. Thus, the article tries to disclose the impacts of environmental degradation and urges to have efficient actions to alleviate the situation with acknowledging and accessing few of initiatives taken, here so forth.